Psychological Status and Quality of Life in relation to the Metabolic Syndrome: Isfahan Cohort Study - Hamidreza Roohafza; Masoumeh Sadeghi; Mohammad Talaei; Zahra Pourmoghaddas; Nizal Sarrafzadegan (International Journal of Endocrinology, 2012)
Objective. Current study was designed to investigate the association of metabolic syndrome (MetS) with depression, anxiety, psychological distress, and quality of life (QoL). Design. Two hundred and fifteen contributors with MetS and 253 participants without MetS were randomly selected from 2151 participants of Isfahan Cohort Study who were residents of Isfahan city. Measurements consisted of fasting blood samples, anthropometrics, and self-reported data of 12-item General Health Questionnaire, Hospital Anxiety and Depression Scale, and European Quality of Life-5 Dimension. Binary logistic regression analysis was used to find the association between MetS and four psychological factors. Results. Participants mean age was 56.3 ± 9.8 years. Male/female ratio was 0.86 (217/251). Mean score of depression (𝑃=0.003), anxiety (𝑃=0.018), distress (𝑃=0.047), and QoL (𝑃≤0.001) was significantly higher in MetS group. There were significant increasing relationships between depression (OR 1.10, 95% CI 1.03–1.22), anxiety (OR 1.03, 95% CI 1.05–1.11), and QoL (OR 1.13, 95% CI 1.05–1.23) and MetS when associations were adjusted for other risk factors, but it was not the case for distress (OR 1.03, 95% CI 0.99–1.08). Conclusion. It might be better to consider MetS as a combination of biological and psychological risk factors. Thus, a person with metabolic disease should be recognized as a patient with these factors and be screened for all of them.